THE EFFECT OF SYNBIOTIC ON RELATIVE WEIGHT OF DUODENUM, JEJUNUM AND ILEUM OF NATIVE CHICKEN - Setyaningrum, Sri; Siregar, Dini Julia Sari; Tarigan, Ruth Riah Ate; Warisman, Warisman (Proceeding International Conference Keputeraan Prof. H. Kadirun Yahya; Vol 1 No 1 (2022): 1st International Conference Keputeraan Prof. Kadirun Yahya, 2022)
The research was to study the effect of synbiotic on relative weight of duodenum, jejunum and ileum of native chicken. A much as of 120 bird native chickens 6 weeks age old used in this study. The study consists of 6 treatments and 4 replicates. The treatments were P0: control, P1: diet with synbiotic 1%, P2: diet with synbiotic 1.5%, P3: diet with synbiotic 2%, P4: diet with synbiotic 2.5% and P5: diet with synbiotic 3.0% of synbiotic. Parameter observed were relative weight of duodenum, jejunum and ileum of native chicken. The result of study showed that the supplementation of synbiotic significat different (p<0.05) on relative weight of duodenum of native chicken but not significant effect on relative weight of jejunum and ileum of native chicken. In conclusion that the supplementation of synbiotic increased the relative weight of duodenum.